2018
DOI: 10.1177/1534735417753541
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ginger in Ameliorating Acute and Delayed Chemotherapy-Induced Nausea and Vomiting Among Patients With Lung Cancer Receiving Cisplatin-Based Regimens: A Randomized Controlled Trial

Abstract: Nausea and vomiting are among the most common and distressing side effects of chemotherapy. Additional antiemetic drugs are urgently needed to effectively manage and ameliorate chemotherapy-induced nausea and vomiting (CINV). The efficacy of ginger as an antiemetic modality for ameliorating CINV has not been established in previous studies. The aim of this study was to examine the efficacy of ginger, as an adjuvant drug to standard antiemetic therapy, in ameliorating acute and delayed CINV in patients with lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
2
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 22 publications
1
51
2
6
Order By: Relevance
“…For example, in a study by Vladimir et al, the ginger-treated group and the diclofenac-treated group received different formulations of drugs, which might have provided information about allocation with high probability [71]. Finally, only eight studies were judged as having low risks for every type of bias based on the Cochrane Collaboration's quality assessment tool [14,18,20,28,29,31,45,55]. Regarding the reporting quality of essential functions, 43 RCTs out of 109 (39.4%) reported a high quality of evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a study by Vladimir et al, the ginger-treated group and the diclofenac-treated group received different formulations of drugs, which might have provided information about allocation with high probability [71]. Finally, only eight studies were judged as having low risks for every type of bias based on the Cochrane Collaboration's quality assessment tool [14,18,20,28,29,31,45,55]. Regarding the reporting quality of essential functions, 43 RCTs out of 109 (39.4%) reported a high quality of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ginger effectively reduced acute and delayed CINV in both children and adults [56,57]. On the other hand, Thamlikitkul et al and Li et al concluded that ginger showed an insufficient effect on the prophylaxis of acute and delayed nausea and vomiting induced by an Adriamycin-cyclophosphamide regimen and a cisplatin regimen, respectively, which are highly emetogenic regimens [19,20].…”
Section: Antiemetic Functionmentioning
confidence: 99%
“…Cisplatin is a widely used chemotherapy for treating various kinds of cancers and belongs to highest emetic agents . It has been reported that cisplatin induced acute, delayed, and chronic pica. Moreover, cisplatin also induces anorexia, weight loss, fatigue, and dyspepsia …”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin is one of the most commonly used drugs in chemotherapy. It is also extremely strong in inducing acute, delayed, and chronic nausea and vomiting, poor appetite, and the loss of body weight in humans and rats. Therefore, we studied dyspepsia induced by cisplatin in a rodent model in our study.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the influence of this intervention on the control of nausea and vomiting in the acute phase, 11 publications were detected that analyzed nausea in the acute phase (15)(16)(22)(23)(24)(25)(26)(27)(28)(29)(30) , among which 8 (23)(24)(25)(26)(27)(28)(29)(30) detected advantages, but only 6 investigations had statistically significant results with p < 5% (p = 0.002 (23) ; p = 0.0001 (24) ; p = 0.04 (26) ; p = 0.0003 (27) , p = 0.003 (29)(30) ). Regarding emesis, 8 studies analyzed the acute stage (14,18,(21)(22)24,(27)(28)34) ; of these, 6 (19,23,25,28,34) observed the therapeutic effect of ginger, but only 2 had significant results considering significance level of 5% (p = 0.002 (29) ; p = 0.04 (35) ). Regarding the influence on the control of nausea and vomiting in the delayed phase, 6 studies (15)(16)(22)(23)(28)…”
Section: Note: Flie: Functional Living Index Emesismentioning
confidence: 99%